Enhancing torrefaction process efficiency for biochar production from filter cake residue in the sugar industry - Rattanachoung, Nopporn (Journal of Applied Research on Science and Technology (JARST), 2024)
The torrefaction process is a promising technique for enhancing the quality of solid biomass fuels. This study investigates the effects of torrefaction on biochar produced from filter cake residue, a byproduct of the sugar industry. The primary objectives were to evaluate the impact of process parameters on biochar properties and identify optimal conditions for maximizing the higher heating value (HHV). Filter cake residue was subjected to torrefaction at temperatures ranging from 220-340°C under an inert atmosphere. The influence of particle size (20, 60, and 100 mesh), nitrogen flow rate (20-30 ml/min), temperature (220-340°C), and residence time (30-90 min) on biochar properties was examined using response surface methodology. Proximate analysis revealed that torrefaction significantly reduced moisture, volatile matter, and ash content while increasing fixed carbon content. The maximum HHV of 21.9571 MJ/kg was achieved at a particle size of 20 mesh, nitrogen flow rate of 25 ml/min, temperature of 340°C, and residence time of 60 min. The experimental results agreed with predicted values from the developed models, with an average error of 3.64%. Optimal torrefaction conditions were determined to be a particle size of 21.77 mesh, nitrogen flow rate of 22.50 ml/min, temperature of 311.13°C, and residence time of 42.58 min, yielding a maximum HHV of 18.4853 MJ/kg. These findings demonstrate the potential of torrefaction for upgrading filter cake residue into a high-quality solid biofuel, providing a sustainable solution for waste utilization in the sugar industry.